The great escape based on a true story - McQueen, Steve 1930-1980; Garner, James; Attenborough, Richard; Donald, James 1917-1993; Bronson, Charles 1920-2003; Pleasence, Donald; Coburn, James; Brickhill, Paul; Bernstein, Elmer; Clavell, James; Burnett, W. R. (William Riley) 1899-1982
In 1943, the Germans open Stalag Luft III, a maximum security prisoner-of-war camp designed to hold even the craftiest escape artists. In doing so, however, they unwittingly assemble the finest escape team in miltary history who plan and execute the largest prison breakout ever attempted.